Rural livelihood vulnerabilities, contributing factors and coping strategies in Takusa Woreda, North Western Ethiopia - Negusie Abuhay Mengistu (Cogent Social Sciences, 2022)
In Ethiopia, rural livelihoods are commonly subjected to diverse social, economic, institutional and natural-induced vulnerabilities, which affect the welfare state of households in rural hemisphere. In spite of that, rural farm households run-through different coping strategies to improve their resilience. Therefore, this study is going to assess the vulnerability context, contributory factors and its coping strategies in Takusa Woreda of North Western Ethiopia. The study employed multistage sampling techniques to select 200 sampled respondents, and descriptive statistics and logit model were employed for analysis. According to the result, on-farm activities include: crop and livestock production were highly vulnerable. Although vulnerabilities were occurred in off-farm and non-farm livelihood activities, households alternatively chooses these livelihood activities in combination with on-farm only strategy. According to the model result, sex, access to irrigation, income, and livestock production risk was significant (p < 0.01). Likewise, crop production risk and total livestock unit were also significant (p < 0.05). Based on the degree of vulnerability contexts rural farm households followed different coping strategies in line with the nature of livelihood strategies. Therefore, Ethiopian livelihood programs is advised to consider household socio-economic contexts and incorporate farm households coping strategies in policy designing to achieve livelihood security.